Molecular evidence for ongoing complementarity and horizontal gene transfer in endosymbiotic systems of mealybugs - López-Madrigal, Sergio; Beltrà, Aleixandre; Resurrección, Serena; Soto, Antonia; Latorre, Amparo; Moya, Andrés; Gil, Rosario (Frontiers in Microbiology, 2014)
Intracellular bacterial supply of essential amino acids is common among sap-feeding insects, thus complementing the scarcity of nitrogenous compounds in plant phloem. This is also the role of the two mealybug endosymbiotic systems whose genomes have been sequenced. In the nested endosymbiotic system from Planococcus citri (Pseudococcinae), “Candidatus Tremblaya princeps” and “Candidatus Moranella endobia” cooperate to synthesize essential amino acids, while in Phenacoccus avenae (Phenacoccinae) this function is performed by its single endosymbiont “Candidatus Tremblaya phenacola”. However, little is known regarding the evolution of essential amino acid supplementation strategies in other mealybug systems. To address this knowledge gap, we screened for the presence of six selected loci involved in essential amino acid biosynthesis in five additional mealybug species. We found evidence of ongoing complementarity among endosymbionts from insects of subfamily Pseudococcinae, as well as horizontal gene transfer affecting endosymbionts from insects of family Phenacoccinae, providing a more comprehensive picture of the evolutionary history of these endosymbiotic systems. Additionally, we report two diagnostic motifs to help identify invasive mealybug species.